Influence of attachment on socio-psychological adaptation and its dynamics in the course of treatment in adolescent patients with schizotypal disorder - O. V. Guseva; A. P. Kotsubinsky; J. D. Zvenigorodskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Summary. Purpose. Study of the influence of attachment quality (based on the analysis of its representation) on the results of treatment and socio-psychological adaptation of adolescent patients with schizotypal disorder.Materials and Methods. 41 adolescents with pseudoneurotic type of schizotypal disorder were surveyed [F 21.3]. All respondents were divided into two groups based on the type of early attachment to mother («reliable attachment» and «unreliable attachment»). A battery of 6 tests was used: a questionnaire for studying of coping-behavior ways (Lazarus R., Folkman С., WCQ, The Waysof Coping Questionnaire, 1988); test LSI, Life style index Plutchik R., Kellerman H., 1979 (in adapt.Wasserman L. I., etc., 1998), the modified questionnaire of attachment ( Yaremchuk M. V., 2005; in modific. Almazova O.V., Burmenskaya G.V., 2015), SCL-90R («Simptom Check List-90-Revised»; Derogatis, Rickels, Rock, 1976), integrative anxiety test (Bizyuk A.P, Wasserman L.I., Iovlev B.V., 2005), scale of assessment of social functioning of patients (Kotsyubinsky A.P., Sheinina N.S., etc. 2013). Studied were the features of protectively-adaptive behavior and the actual psychological symptomatic status, indicators of personal and situational anxiety, as well as features of contact with the doctor, and dynamics of indicators of social adaptation during treatment.Results. Confirmed the relationship of representation unreliable type of attachment to the mother, in patients with schizotypal disorder, and sustained violation in the sphere of relationships with parents, disorders of emotional regulation, reduce psychological adaption in general. In such patients, during the treatment process, lower compliance indicators, specific features of the protective-coping style of behavior, as well as slower rates of psychological and social recovery were revealed.Conclusion. According to the results of the study, data indicating the negative impact of unreliable attachment in adolescent patients with schizotypal disorder on psychological recovery during treatment and socio — psychological adaptation of patients in general were obtained. Psychotherapeutic recommendations are presented.